Awareness of occupational hazards and utilization of PPE amongst welders in Jos metropolis, Nigeria - Tagurum, Yetunde O.; Gwomson, Martin D.; Yakubu, Pankyes M.; Igbita, James A.; Chingle, Moses P.; Chirdan, Oluwabunmi O. (International Journal of Research in Medical Sciences, 2018)
Background: Welding poses a range of both well-known and subtle hazards to health and safety. These hazards can act quickly or may show up only in the long term. They can be rapidly fatal (electric shock or exposure to cadmium fumes) or have delayed effects (lung changes over time). This study aimed to assess the awareness of occupational hazards and utilization of PPE amongst welders in Jos metropolis. Methods: This was a descriptive, cross-sectional study involving 295 welders in Jos metropolis. An interviewer-administered questionnaire was used to collect data which was entered and analyzed using Epi-info version 3.5.4 statistical software. A probability value of p≤0.05 was considered statistically significant. Results: All the respondents were males with a mean age of 24.6±7.7 years. The study revealed that 293 (99.3%) were aware of occupational hazards in welding. In this study, goggles were the most frequently used PPE 98%, then gloves 65.4%, boots 58%, overalls 36.3%, facemask 30.6% and earplugs 12.9%. A statistically significant (p≤0.05) relationship was found between employment pattern as well as working hours per day and the use of safety devices. Conclusions: The study showed that most of the welders had fair knowledge of welding related health problems, hazards and safety devices, and utilization of safety devices was less than optimal. An educational campaign on workplace hazards, types and proper use of different personal protective devices should be instituted for welders on a regular basis by the welders association, local and state government.